(untitled) (Bangladesh Journal of Zoology, 2018)
This study was conducted to assess the divesity of Orthopteran species at some grasslands and crop fields of Keranigonj upazila in Dhaka district, Bangladesh from April, 2014 to September, 2014. A total of 20 species under 18 genera belonging to 7 families have been recorded. Among them 4 species were more common, 6 species were moderately distributed and 10 species documented as rare. The highest number of Orthopterans was from the family Acrididae 60.58% (10 spp.) followed by Tetrigidae 15.32% (2 spp.), Gryllidae 14.23% (4 spp.), Tettigonidae 10.33% (1 sp.), Locustidae 2.55% (1 sp.), Mantidae 2.55% ( 1 sp.), and the lowest from the family Gryllotalpidae 2.19% (1 sp.). During observation period the number of Orthopterans was highest recorded in the month of May (20.44%) followed by April (19.34%), June (17.52%), July (14.60%), August (14.23%), and the lowest in September (13.87%). Shannon’s diversity index and Simpson’s diversity index represent moderate value (H = 2.82) and moderately low value (λ = 0.07), respectively indicating moderate diversity richness for Orthopteran species. The value of species evenness (E = 0.94) tends to be higher indicating that the species are eventually distributed. Bangladesh J. Zool. 46(1): 21-31, 2018